Development of Interactive Media Flipbook to Improve Students' Critical Thinking Skills on Earth Rotation and Revolution Material in Grade VI Elementary School - Putri Fatimattus Azzahra; Ludfi Arya Wardana; Didit Yulian Kasdriyanto; Ribut Prastiwi Sriwijayanti (Postgraduate, University of Mataram, 2025)
This research is based on the need for learning media that can improve students' critical thinking skills in understanding the material of Earth's Rotation and Revolution. Interactive Flipbook media was chosen as a solution because of its ability to present learning content in an interesting and interactive way, which is in accordance with the demands of 21st century education. The research was conducted at SDN Al-Amin Probolinggo by involving grade VI students as research subjects. This research uses the Research & Development (R&D) method with the ADDIE model which includes five stages: Analysis - identifying learning media needs through observation; Design - designing interesting and interactive Flipbook content; Development - developing and validating learning media; Implementation - testing the media on grade VI students; and Evaluation - analyzing the effectiveness of the media. This research aims to produce the validity, practicality and effectiveness of the Interactive Flipbook Media. The results of the study showed a validity level of 92.42%, practicality of 93.75%, and effectiveness of 100% with all students achieving KKM, proving that Interactive Flipbook media is effective in improving students' critical thinking skills.